Exploring the Meaning Behind the Determination of Integrated Public Transportation Fares: A Paul Ricoeur Hermeneutic Study - Muhamad Saladin; M. Irfan Tarmizi (Eduvest - Journal of Universal Studies, 2026)
This research aims to uncover the meaning behind the determination of public transportation integration tariffs in Jakarta by using the interpretive paradigm and the hermeneutic approach of Paul Ricoeur. Integration tariffs are understood not solely as a technocratic instrument or economic decision, but as a social text that contains values, symbols, and policy narratives built through interactions between governments, transportation operators, system managers, and user communities. The research method used was qualitative with data collection techniques in the form of in-depth interviews with key informants from the DKI Jakarta Provincial Transportation Office, the Jakarta City Transportation Council (DTKJ), the management of PT Jakarta Lingko Indonesia, and the transportation user community, and supported by a study of related policy documentation. Data analysis is carried out through three stages of Ricoeur's hermeneutics, namely semantic, reflective, and existential stages. The results of the study show that the integration tariff is interpreted as a symbol of inclusivity that includes accessibility, equality, mobility justice, and welfare, and represents the presence of the state in guaranteeing the mobility rights of city citizens. Integration tariffs not only serve to reduce transportation system fragmentation and travel cost burdens, but also shape a more humane, equitable, and sustainable mobility experience. Thus, the determination of integration tariffs is a policy narrative that reflects the relationship between the state, technology, and society in building a public transportation system that is oriented towards social justice and the future of the city of Jakarta.